Matricellular proteins as modulators of wound healing and the foreign body response - Kyriakides, Themis R.; Bornstein, Paul (Thrombosis and Haemostasis, 2003)
Matricellular proteins form a group of extracellular matrix (ECM) proteins that do not subserve a primary structural role, but rather function as modulators of cell-matrix interactions (1). Members of the group, including thrombospondin (TSP) -1, TSP-2, SPARC, tenascin (TN)-C, and osteopontin (OPN), have been shown to participate in a number of processes related to tissue repair. Specifically, studies in knockout mice have indicated that a deficiency in one or more of these proteins can alter the course of wound healing. More recently, TSP1, TSP2, and SPARC have also been implicated in the foreign body response, an unusual reaction to injury that occurs after the implantation of biomaterials. This review will focus on the roles of these proteins in the response to injury in mice and will show how studies of this pathophysiological process can elucidate some of the intrinsic properties of these matricellular proteins.
Keywords: Matricellular proteins; wound healing; foreign body response; thrombospondin; cell-matrix interactions